PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN DENGAN ANGGARAN SEBAGAI ALAT PENGENDALIAN BIAYA PADA PT. KERETA API LOGISTIK - Ruchan Sanusi, Ruchan Sanusi (Fakultas Ekonomi Universitas 45 Surabaya, 2019)
A responsibility accounting is an accounting system which accrued the exitense of responsibility centers in a corporation. This is caused by given authority and how to account it for in written report. The report could be a responsibility report that could use as a analyzing refference of mnagerial performance for each responsibility centers and cost controller. In this case, cost is linked to the manager who have an authority to dispose the resources hence, the resources must be nonfied in currency, so responsibility accounting is a cost controling method which enable management to manage cost. This reearch use qualitative approach. This research also use divining manual study and interview with accounting staff of PT. Kereta Api Logistic to abtain data. From result of research in PT. Kereta Api Logistic, the company have not applied responsibility accounting well enough, this matter an be known based on any qualifications and characteristic which have not been fulfilled. The company also have not implement cost control well, this matter can be seen from analysis for cost variance that have not been done.